Estratégias de resolução de problemas de otimização. - Saldanha, Ingrid Vieira (2020)
This work aims to present three strategies for solving problems of optimization, involving some geometric concepts such as areas of flat figures and volume geometric solids. We will present a method using differential calculus and, two others without the use of calculus. For this, we will initially deal with the main theorems to be respect to calculation and then some concepts of geometry, fundamental to the solving the problems that will be presented. Based on that, two resolution strategies, one with the use of maximum and minimum values ​​of a function quadratic and, later, another, through the use of inequality of means. We will end with the third strategy, addressing geometric problems, using the theorems calculations presented at the beginning. For this work, the methodology used was the bibliographic research. Through this research, we were able to conclude that, despite the three presented, the calculation takes on great importance for the resolution of this type of problem, since there are a lot of situations that cannot be solved through the inequality of means, nor with the use of the quadratic function.